Analisis Kesulitan Belajar pada Anak Berkebutuhan Khusus (ABK) Di SMA Negeri 10 Kota Ternate - Dewi Mufidatul Ummah (Jurnal Bimbingan dan Konseling Terapan, 2018)
This study aims to determine the analysis of learning difficulties in children with special needs (ABK) in students of SMA Negeri 10 Ternate. This research is descriptive research using descriptive approach. The focus of this study is focused on learning problems in students with special needs (ABK) on Deaf and Tuna Grahita in students of SMAN 10 Kota Ternate. The types and sources of data in this study consist of primary and secondary data that are qualitative in nature. Data collection techniques consist of interviews, observations, and documentation. Data Analysis Technique used is data reduction (reduction), Presentation of data (display), Verification Data (verification). The technique of data validation in this research is Triangulation and Member check. The results showed that SRN subjects showed low learning outcomes, were slow in doing learning tasks, were unable to capture material explanations, never collected and completed tasks and were difficult to adapt to the learning process at school. The SC subject shows the result that the SC Subject has below average intellectual ability and lack of confidence, learning difficulties experienced by SC subjects on all subjects related to practice and theory. SC learning difficulties are caused by psychic limitations of slow response and slow learner in receiving lessons and still difficult to write and read.